Research on the influence of dynamic contact angle of mercury meniscus on the interpretation of rock pore throat radius in mercury intrusion experiments - Dai, Jinyou; Pi, Sha; Wu, Junzhe; Zhang, Yang (Frontiers in Earth Science, 2024)
Utilizing the withdrawal curve O and the secondary injection curve R measured by the mercury intrusion porosimetry, a new type of closed mercury intrusion characteristic curve (O-R curve) is constructed. Based on the good wettability and dewetting correlation characteristics at the equal mercury saturation points of this curve, a method for calculating the dynamic contact angle of mercury meniscus (O-R loop method) is established. Taking the Chang 63 tight oil reservoir rock samples from Nanliang Oilfield in the Ordos Basin of China as an example, this method is used to study the effect of the dynamic contact angle of mercury meniscus on the interpretation of rock pore throat radius in mercury intrusion porosimetry experiments. The results show that the dynamic contact angle of mercury meniscus changes significantly during mercury intrusion porosimetry experiments, which cannot be ignored. And the smaller the pore throat is, the more severe the deformation of mercury meniscus is, and the greater the wetting resistance coefficient and hysteresis angle are. Besides, the rock pore throat radius interpreted by the modified Washburn equation (using dynamic contact angle) is generally larger than that of the conventional Washburn equation (using static contact angle) through calculations, with a relative error ranging from 12.2% to 54.7%. The smaller the pore throat is, the greater the relative error is. The analysis shows that the conventional Washburn equation significantly underestimates the reservoir pore throat radius due to the neglect of the dynamic contact angle, while the modified Washburn equation provides more accurate interpretation. Overall, this research provides a method for calculating the dynamic contact angle in mercury intrusion porosimetry experiments and has important reference significance for the accurate interpretation of rock pore throat radius.